Sodium bicarbonate supplementation prevents skilled tennis performance decline after a simulated match - Wu, C.; Shih, M.; Yang, C.; Huang, M.; Chang, C. (Journal of the International Society of Sports Nutrition, 2010)
The supplementation of sodium bicarbonate (NaHCO3) could increase performance or delay fatigue in intermittent high-intensity exercise. Prolonged tennis matches result in fatigue, which impairs skilled performance. The aim of this study was to investigate the effect of NaHCO3 supplementation on skilled tennis performance after a simulated match. Nine male college tennis players were recruited for this randomized cross-over, placebo-controlled, double-blind study. The participants consumed NaHCO3 (0.3 gkg-1) or NaCl (0.209 gkg-1) before the trial. An additional supplementation of 0.1 gkg-1 NaHCO3 or 0.07 gkg-1 NaCl was ingested after the third game in the simulated match. The Loughborough Tennis Skill Test was performed before and after the simulated match. Post-match [HCO3-] and base excess were significantly higher in the bicarbonate trial than those in the placebo trial. Blood [lactate] was significantly increased in the placebo (pre: 1.22+/-0.54; post: 2.17+/-1.46 mM) and bicarbonate (pre: 1.23+/-0.41; post: 3.21+/-1.89 mM) trials. The match-induced change in blood [lactate] was significantly higher in the bicarbonate trial. Blood pH remained unchanged in the placebo trial (pre: 7.37+/-0.32; post: 7.37+/-0.14) but was significantly increased in the bicarbonate trial (pre: 7.37+/-0.26; post: 7.45+/-0.63), indicating a more alkaline environment. The service and forehand ground stroke consistency scores were declined significantly after the simulated match in the placebo trial, while they were maintained in the bicarbonate trial. The match-induced declines in the consistency scores were significantly larger in the placebo trial than those in the bicarbonate trial. This study suggested that NaHCO3 supplementation could prevent the decline in skilled tennis performance after a simulated match.